FRI0177 Time To Achieve Remission Predicts Long Term Survival of Low-Dose Etanercept: An Observational Study. (15th July 2016) - Ometto, F.; Raffeiner, B.; Botsios, C.; Friso, L.; Astorri, D.; Bernardi, L.; Punzi, L.; Doria, A.
Abstract : Objectives: To investigate survival of low-dose etanercept (ETN) (25 mg weekly) and possible predictors. Methods: We collected retrospectively data of RA patients starting ETN between April 2001 and September 2014 who achieved and maintained low-dose ETN for at least 12 months. Patients were evaluated every 3 months. Patients who achieved and maintained remission (DAS28 <2.6) for at least 6 months started low dose ETN. If remission was lost in two consecutive visits the patient returned to full dose. We recorded the time to achieve remission (TTR), the time in which ETN dose was reduced since remission (TRL) and the time in which patients returned to full dose or were switched to other biologics. Variables collected are reported in Table I. Survival was analysed with Cox-regression. Results: Among 532 patients, 276 were excluded because of missing data or because they were lost from follow-up leaving 256 patients eligible. After 11.28±4.05 years, 151/256 (59.0%) maintained half dose (Table 1 ). TTR, and TRL were associated to low-dose failure (Table 1 ) and correlated with each other (TTR and TRL R 0.45, p<0.001). We run two separate analyses for TTR and TRL, covariates were positive rheumatoid factor or anti-citrullinated peptides and mean prednisone dose. TTR was a significant predictor of low-dose failure (OR 1.50 per year increase, 95% C.I. 1.34–1.68, p<0.001) while TRL was not (Table 2). Conclusions: A shorter TTR is a predictor of long-term survival of low-dose ETN. Disclosure of Interest: None declared